RESULT OF SEVERAL CLONE OF SWEET POTATO (Ipomoea batatas L.) IN MIDDLE EAST ON THE INFLUENCE OF PHOSFOR FERTILIZER DOSAGE AND CLONE TYPES - Mardhiah Hayati; Rita Hayati (UPT Penerbitan Universitas Jember, 2017)
Sweet potatoes include commodities as the main source of carbohydrates that occupy thefifth position after rice, cassava, wheat and corn. These plants can be cultivated at variousaltitude places in the lowlands, middle and highlands. Judging from the nutritional value ofsweet potatoes have the privilege as an important source of carbohydrates so that thiscommodity becomes an alternative for food diversification program. The purpose of thisstudy is to determine the effect of phosphorus fertilizer dosage and clone type andinteraction between the two treatments on sweet potato yield in the middle plains. Thisresearch was conducted at Suka Makmur Village Farmer Kecamatan Lembah Selawah Districtof Aceh Besar Saree, at an altitude of 560 m above sea level from February to June 2016. Thisstudy used a Randomized Block 3 factorial factorial design with 3 replications consisting of 2Factor, ie treatment of phosphorus fertilizer dosage and clone type. The phosphorusphosphorus treatment (SP 36) consisted of 3 levels, 100, 200 and 300 kg / ha and clone typefactor ie CIP BDG, Local Saree Krem, and Antin 1. The variables observed in this study werewet bulb weight, Dry tuber weight, number of tubers, general evaluation of tubers and tuberproduction per hectare. The results showed that treatment of SP 36 fertilizer dosage was notsignificant on wet bulb weight, tuber weight, tuber amount, general evaluation of tubers andtuber production per hectare. The dose of SP 36 fertilizer tends to be better at a dose of 200kg / ha. The clone type had a significant effect on the number of tubers and significantlyaffected the wet bulb weight, the weight of tubers and tuber yield per hectare and did notsignificantly affect the general evaluation of tubers. The best clone type is Local Creme Saree.There is no significant interaction between the treatment of SP 36 fertilizer dosage and theclone type on sweet potato crops.